Computational flow analysis of different streamline cooling plates for thermal management of lithium-ion battery. Issue 1 (31st December 2022) - Shetty, Divya D; Venugopal, Vivek; R, Pradeep; Zuber, Mohammad; Anjum Badruddin, Irfan; Kini, Chandrakant
Abstract: The Li-ion batteries used in electric vehicles widely employ cooling plates with mini channels for thermal management purpose. Researches on battery thermal management systems of electric vehicles are largely focused on improving the cooling efficiency hence obtaining temperature uniformity across the cells. In the present work, a streamline configuration has been incorporated in cooling plate design to enhance the performance of mini-channel cooling plate. These kinds of configurations are usually found in submarine and aerospace applications. By adopting streamline design the flow resistance is found to reduce. Five plates with different number of channels (3, 4, 5, 6, 7) were computationally studied at a coolant (water and ethylene glycol mixture) flow rate of 0.002 kg/s. The maximum cell temperature is decreased by 7.8% for 7-channel configuration. Temperature uniformity is also found to improve using this design. The results reveal that this design is able to maintain the temperature of Li-ion battery in safe operating range. Hence this could be a better solution for thermal management of Li-ion batteries in future.